Digital Communication And Social Pressure: Analysis Of The Fomo Phenomenon Among Young People - Ganesha Ayu Praditara; Abel Lisa Oktarina; Sri Narti (Utami Publisher, 2026)
The development of digital communication through social media has reshaped patterns of social interaction among young people, particularly university students. The high intensity of social media use not only influences communication practices but also generates social pressure that affects individuals’ emotional conditions and behaviors. One phenomenon that emerges as a result of this digital social pressure is Fear of Missing Out (FOMO). This study aims to analyze how digital communication creates social pressure and triggers FOMO among university students. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, non-participant observation, and documentation involving students aged 18–25 who actively use social media. The findings indicate that repeated exposure to social media content forms digital social norms that encourage students to constantly engage in social activities. This social pressure strengthens social comparison processes and leads to feelings of anxiety, fear of being left out, and the tendency to force oneself to follow trends or social activities. FOMO not only affects emotional well-being but also influences students’ social behavior and consumption patterns. The study concludes that FOMO is a consequence of digital communication dynamics and social pressure on social media, highlighting the importance of digital literacy to foster healthier communication practices among students.